Canadian immigration and refugee law: a practitioner's handbook - Desloges, Chantal (Emond Montgomery Publications Limited, 2024)
"This title is the fourth edition of our flagship professional immigration title, originally adapted from Lynn Fournier-Ruggles’ Canadian Immigration and Refugee Law for Legal Professionals, 3rd Edition. Aimed at young lawyers and consultants, it offers a broad and practical treatment of Canadian immigration, refugee, and citizenship law."– Provided by publisher.